1998
DOI: 10.1172/jci610
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 stimulates luteinizing hormone-releasing hormone secretion in a rodent hypothalamic neuronal cell line.

Abstract: To examine the influence of the putative satiety factor (GLP-1) on the hypothalamo-pituitary-gonadal axis, we used GT1-7 cells as a model of neuronal luteinizing hormone- releasing hormone (LHRH) release. GLP-1 caused a concentration-dependent increase in LHRH release from GT1-7 cells. Specific, saturable GLP-1 binding sites were demonstrated on these cells. The binding of [125I]GLP-1 was time-dependent and consistent with a single binding site (Kd = 0.07+/-0.016 nM; binding capacity = 160+/-11 fmol/mg protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 52 publications
2
78
0
Order By: Relevance
“…The present results, however, argue against this hypothesis, at least with respect to fluid intake, because the central injection itself did not decrease water intake. Furthermore, the findings suggest that the LV injection itself is not, in fact, a stressor because previous studies of stress and fluid intake found that either mild or severe stressors increase, rather than decrease, fluid intake (Deaux and Kakolewski, 1970;Vaswani et al, 1983;Bourjeili et al, 1995). This does not discount a role of GLP-1 in stress, but it does suggest that any effect of GLP-1 on stress is separate from its effects on fluid intake.…”
Section: Discussionmentioning
confidence: 84%
“…The present results, however, argue against this hypothesis, at least with respect to fluid intake, because the central injection itself did not decrease water intake. Furthermore, the findings suggest that the LV injection itself is not, in fact, a stressor because previous studies of stress and fluid intake found that either mild or severe stressors increase, rather than decrease, fluid intake (Deaux and Kakolewski, 1970;Vaswani et al, 1983;Bourjeili et al, 1995). This does not discount a role of GLP-1 in stress, but it does suggest that any effect of GLP-1 on stress is separate from its effects on fluid intake.…”
Section: Discussionmentioning
confidence: 84%
“…Whether this could play a significant role during long-standing hypoglycemia is not clear. The presence of GLP-1 receptors on somatotropic cells is a possibility, as previous reports have demonstrated that GLP-1 is able to modify hypothalamic and other pituitary functions (24,25). One may hypothesize differential binding to receptors between GLP-1 and exenatide or the presence of polymorphic receptors.…”
Section: Discussionmentioning
confidence: 95%
“…Corticosterone was measured using a commercial RIA Kit (MP Biomedicals, Loughborough, Leicestershire, UK). Prolactin was analysed by RIA using reagents and methods provided by the National Institute of Diabetes and Digestive and Kidney Diseases and the National Hormone and Pituitary Program as previously described (Beak et al 1998). Hypothalamic hormones (CRH and AVP) were assayed using in-house assays as previously described (Wren et al 2002).…”
Section: Hormone Assaysmentioning
confidence: 99%